Structure of motive preparedness of girls of midchildhood - Худолій, О. М.; Мірошниченко, Д. Т. (Physical Education Theory and Methodology, 2012)
The article is sanctified to the analysis of structure of motive preparedness of girls of midchildhood. On the basis of data of experiment there is a certain structure of motive preparedness of girls, methodical recommendations are worked out to priority development of motive capabilities for the girls of midchildhood.